Awaiting accurate scientific evidence: Progression or “profiles” in bipolar disorder? - Martino, Diego Javier (2017)
This letter is written in response to a review recently published in the journal. The aim is to highlight a potential meth- odological limitation common to many studies comparing bipolar patients with few previous episodes versus those with multiple episodes, and in which the results are interpreted as indicating the longitudinal course of the illness.